2020
DOI: 10.1002/advs.202001526
|View full text |Cite
|
Sign up to set email alerts
|

Charge Redistribution Caused by S,P Synergistically Active Ru Endows an Ultrahigh Hydrogen Evolution Activity of S‐Doped RuP Embedded in N,P,S‐Doped Carbon

Abstract: Water splitting for production of hydrogen as a clean energy alternative to fossil fuel has received much attention, but it is still a tough challenge to synthesize electrocatalysts with controllable bonding and charge distribution. In this work, ultrafine S‐doped RuP nanoparticles homogeneously embedded in a N, P, and S‐codoped carbon sheet (S‐RuP@NPSC) is synthesized by pyrolysis of poly(cyclotriphosphazene‐co‐4,4′‐sulfonyldiphenol) (PZS) as the source of C/N/S/P. The bondings between Ru and N, P, S in PZS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…A potential solution to the aforementioned challenge is homogeneous heteroatom doping, which is capable of concurrently modulating both the bulk electronic structures and geometric surface structures of catalysts. [ 29–33 ] However, strategies for homogeneous doping remain limited and are characterized by certain drawbacks. For instance, hydrothermal and solvothermal approaches are applicable only for homogeneous metal doping.…”
Section: Introductionmentioning
confidence: 99%
“…A potential solution to the aforementioned challenge is homogeneous heteroatom doping, which is capable of concurrently modulating both the bulk electronic structures and geometric surface structures of catalysts. [ 29–33 ] However, strategies for homogeneous doping remain limited and are characterized by certain drawbacks. For instance, hydrothermal and solvothermal approaches are applicable only for homogeneous metal doping.…”
Section: Introductionmentioning
confidence: 99%
“…Doping with various non-metal elements can also improve the HER activity of Ru-based catalysts through the coordination effect. Zhou et al [ 36 ] reported ultrafine S-doped RuP nanoparticles being homogeneously embedded in an N-, P-, and S-codoped carbon sheet (S-RuP@NPSC) by pyrolysis. The mass activity was 22.88 times that of Pt/C at an ultra-low loading of 0.8 wt%.…”
Section: Electronic Effect Modulationmentioning
confidence: 99%
“…[ 46 ] Also, a comparison of the Fourier transforms of EXAFS and fitting results at the Ni K‐edge of the different samples is applied to extract the structural parameters (Figure 3e). [ 47–48 ] The Ni−Ni(Fe) bond distance in NiFeP@NC/Ni 2 P is slightly shorter than that of Ni 2 P (Table S1, Supporting Information), meaning the Ni−Ni(Fe) bond strengthening and demonstrating an intimate interfacial contact of edge‐occupied Fe species with interconnected Ni 2 P nanoparticles. [ 43,44 ] The Fourier transforms of EXAFS and fitting results at the Fe K‐edge reveal a distinguished position difference of Fe−P and Fe−Fe(Ni) bond in NiFeP@NC/Ni 2 P as compared with those in Ni 2 P–FeP@NC (Figure 3h and Table S2, Supporting Information).…”
Section: Figurementioning
confidence: 99%